The effects of replacing fish meal or soy protein concentrate with wheat gluten on growth, whole-body composition, and the retention and apparent digestibility coefficient of amino acids in Japanese seabass (Lateolabrax japonicus) - Zhang, Yuexing; Wang, Linghua; Dong, Zhiyong; Changarawe, Samwel Mugeni; Huang, Liying; Hu, Jinwei; Storebakken, Trond; Shi, Bo (Frontiers in Physiology, 2023)
The aim of this study was to evaluate the effects of replacing fish meal (FM) or soy protein concentrate (SPC) with wheat gluten on growth performance, feed utilization, and nutrient digestibility and retention in Japanese seabass (Lateolabrax japonicus). Seven isonitrogenous (441–456 g kg−1 crude protein) and isocaloric (21.5–22.0 MJ kg−1 gross energy) diets were produced to replace 0%, 33.3%, 66.7% and 100% of FM or SPC with a mixture of wheat gluten, wheat, and taurine (GWT, 77.5% wheat gluten, 20.5% wheat and 2.0% taurine). The gradual replacement of protein in FM with GWT had no significant effects on feed intake, whole-body composition, and the hepatosomatic and viscerosomatic indices, but resulted in a linear decrease in the weight gain rate, feed efficiency, and retention of nitrogen, energy, and essential amino acids (Arg, His, Ile, Leu, Lys, Met, Phe, Thr, and Val). The apparent digestibility of most essential amino acids (Cys, His, Leu, Lys, and Phe) and total amino acids increased linearly. Replacement protein in SPC with GWT had no significant effects on feed intake, growth, the feed conversion ratio, whole-body composition, and the hepatosomatic index, but resulted in a linear decrease in nitrogen, energy, and Met retention; the digestibility of Cys and Met increased linearly. Overall, wheat gluten is a more effective alternative for replacing protein in SPC than FM.